Erratum: JUDSON, MARK L.I. (2012) Nomenclatural problems associated with the generic names Obisium Leach, 1814, Blothrus Schiödte, 1847 and Neobisium Chamberlin, 1930 (Arachnida: Chelonethi). Zootaxa, 3475, 21–35. - Judson, Mark L.i. (Zootaxa, 2012)
(Erratum)